2011
DOI: 10.1378/chest.10-3147
|View full text |Cite
|
Sign up to set email alerts
|

Lung MRI as a Possible Alternative to CT Scan for Patients With Primary Immune Deficiencies and Increased Radiosensitivity

Abstract: Lung alterations in patients with higher radiation sensitivity, such as patients with CVID, might be evaluated by MRI, a radiation-free technique alternative to CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 31 publications
0
54
0
3
Order By: Relevance
“…The main limitation is that we evaluated a single sequence, which may have influenced the sensitivity of MRI to detect CF lung disease. We used a single sequence study design as in prior publications [13,14] because we wanted to assess whether the motion correction technique of PROPELLER would have resulted in improved image quality in chest MRI by reducing the impact of respiratory movements [26]. However, a potential limitation of the use of PROPELLER is that this sequence can produce streak artefacts related to the K-space reconstruction [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation is that we evaluated a single sequence, which may have influenced the sensitivity of MRI to detect CF lung disease. We used a single sequence study design as in prior publications [13,14] because we wanted to assess whether the motion correction technique of PROPELLER would have resulted in improved image quality in chest MRI by reducing the impact of respiratory movements [26]. However, a potential limitation of the use of PROPELLER is that this sequence can produce streak artefacts related to the K-space reconstruction [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…areas of collapse and consolidation, bronchiectasis and bronchial wall thickening [87] or with alveolar haemorrhage [88], can be seen on MRI as a nonspecific airspace-filling process, similar to findings on a CT scan, and may provide similar information to a CT scan without the increased radiation exposure; these modalities are increasingly used. MRI with diffusion weighted imaging has been shown to be a reliable technique to detect lung alterations in patients with various immunodeficiency diseases [89,90]. CT scans and MRI findings were comparable for moderate-to-severe degrees of bronchial and parenchymal alterations.…”
Section: Risks Of Diagnostic Radiation In A-tmentioning
confidence: 97%
“…Findings such as bronchial dilatation, signet ring sign (large airway involvement), tree-in-bud sign (small airway involvement), mucopurulent plugs, bronchial wall thickening, lack of tapering, and bronchi visible closer than 2 cm to the pleural surface are considered characteristic of bronchiectasis [92]. Since we and others demonstrated that patients with DNA repair defects and some CVID patients show increased radiation sensitivity [93][94][95], a radiation-free alternative to CT scan or chest X-ray could be magnetic resonance imaging to assess pulmonary changes and alterations [96]. Recognizing the cause of bronchiectasis may improve management and prognosis, eg, initiation of immunoglobulin replacement in PAD patients, which may prevent the progression of irreversible lung damage.…”
Section: Bronchiectasismentioning
confidence: 99%